Global trends in pediatric burn injuries and care capacity from the World Health Organization Global Burn Registry - Jordan, Kelly C.; Di Gennaro, Jane L.; von Saint André-von Arnim, Amélie; Stewart, Barclay T. (Frontiers in Pediatrics, 2022)
Burn injuries are a major cause of death and disability globally. The World Health Organization (WHO) launched the Global Burn Registry (GBR) to improve understanding of burn injuries worldwide, identify prevention targets, and benchmark acute care. We aimed to describe the epidemiology, risk factors, and outcomes of children with burns to demonstrate the GBR’s utility and inform needs for pediatric burn prevention and treatment. We performed descriptive analyses of children age ≤18 years in the WHO GBR. We also described facility-level capacity. Data were extracted in September of 2021. There were 8,640 pediatric and adult entries from 20 countries. Of these, 3,649 (42%) were children (0-18 years old) from predominantly middle-income countries. The mean age was 5.3 years and 60% were boys. Children aged 1-5 years comprised 62% (n=2,279) of the cohort and mainly presented with scald burns (80%), followed by flame burns (14%). Children >5 years (n=1,219) more frequently sustained flame burns (52%) followed by scald burns (29%). More than half of pediatric patients (52%) sustained a major burn (≥15% total body surface area) and 48% received surgery for wound closure during the index hospitalization. Older children had more severe injuries and required more surgery. Despite the frequency of severe injuries, critical care capacity was reported as ‘limited’ for 23% of pediatric patients. Children represent a large proportion of people with burn injuries globally and often sustain major injuries that require critical and surgical intervention. However, critical care capacity is limited at contributing centers and should be a priority for healthcare system development to avert preventable death and disability. This analysis demonstrates that the GBR has the potential to highlight key epidemiological characteristics and hospital capacity for pediatric burn patients. To improve global burn care, addressing barriers to GBR participation in low- and low-middle-income countries would allow for greater representation from a diversity of countries, regions, and burn care facilities.